Tauroursodeoxycholic acid, a bile acid, is neuroprotective in a transgenic model of Huntington's disease - Keene, CD (2015)
Huntington's disease (HD) is an untreatable neurological disorder caused by selective and progressive degeneration of the caudate nucleus and putamen of the basal ganglia. Although the etiology of HD pathology is not fully understood, the observed loss of